Pengaruh produk domestik regional bruto sektor pertanian, upah minimum provinsi dan investasi terhadap penyerapan tenaga kerja pada sektor pertanian Kabupaten Batanghari - Toher Junrillah; Junaidi Junaidi; Nurhayani Nurhayani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
In this research, the primary purpose is to know and analyze the impact of gross domestic, regional products in the agriculture sector, local minimum salary, and investing toward employment in the agriculture sector in Batanghari District. This research was carried out in Batanghari District, Jambi Province, using secondary data for 19 years since 2000-2018, Sourced from Badan Pusat Statistik (BPS). The data analysis model is econometric using multiple regression analysis methods using SPSS version 22 as the research data processor. According to the estimation result, it was found partially, PDRB agriculture sector has a positive impact and is significant toward employment in the agriculture sector in Batanghari District. At the same time, local minimum salary variables and investment do not positively impact a career in Batanghari District.  Keywords: Employment, PRDB in the agriculture sector, provincial minimum salary, investment